Analisis Pengaruh Demokrasi , Indeks Gini dan Upah Minimum Provinsi Terhadap Pertumbuhan Ekonomi di Indonesia - Adib Adib; Idris Idris; Mike Triani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This study aims to know and analyze the influence of Democracy, Gini and Province Minimum Wages to Economic Growth in Indonesia. The data used are panel data from 33 Provinces in Indonesia during the period 2010-2016. The type of research used is descriptive and associative. The type of data used is secondary data. This research uses Random Effect Model (REM) approach.The results of this study indicate that: (1) Indonesian Democracy Index has no significant effect on Economic Growth in Indonesia, (2) Gini index has negative and significant impact on Economic Growth in Indonesia; (3) Province Minimum Wage has positive and significant impact on Economic Growth in Indonesia., (4) Indonesia Democracy Index, Gini Index, Province Minimum Wage have a significant effect on Economic Growth in Indonesia. Suggested to the government should pay more attention to the condition of Democracy, Gini Index and Provincial Minimum Wage, because then it can give influence to economic growth in Indonesia.